Influence of layered structure of composite timber floor boards on their hardness : Utjecaj strukture slojeva na tvrdoću višeslojnih podnih obloga - Borysiuk, Piotr (Array, 2019)
The possibility of using composite elements of flooring pine veneers with knotholes for the production of supporting layers has been determined. This assessment was made on the basis of the Brinell hardness measurement of the face layer of five-layer composites with empty spots in their structure imitating knotholes of various diameters (10, 20 and 50 mm). The dependencies obtained from empirical determinations were supported by numerical analysis. It was found that it is possible to use veneers with defects (empty spots) with a diameter of up to 20 mm to produce composites of three and more layers of wood (counting from the face layer). The anatomical section of the exposed wood on the face (radial cross-section, tangential section) of the layered composite does not affect the obtained hardness values.